A Cyclical Nurse Schedule Using Goal Programming - Ruzzakiah Jenal; Wan Rosmanira Ismail; Liong Choong Yeun; Ahmed Oughalime (Journal of Mathematical and Fundamental Sciences, 2011)
Scheduling is a very tedious task in organizations where duty is around the clock. Constructing timetable for nurses in hospital is one of the challenging jobs for the head nurse or nurse manager. It requires a lot of time to spend for generating a good and fair timetable. Thus, in this study, we propose a cyclical nurse scheduling model using a 0-1 goal programming that would help the head nurse or nurse manager to have less effort on building new schedules periodically. The proposed model satisfies the stated hospital's policies and the nurses' preferences. The result obtained from this model gives an optimal solution where all goals are achieved. The model also provides an unbiased way of scheduling the nurses and thus leads to an overall higher satisfaction and fairness to the nurses and the hospital management.